Climate Analogues tool training in Nairobi, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The “Using climate scenarios and Analogues for Designing Adaptation Strategies in East Africa” training session was held at ILRI campus in Nairobi from the 7th to 10th of August, 2012. Led by Dr. Ousmane Ndiaye (Meteorological Service, Senegal) and Flora Mer (CIAT, Colombia), the training session aimed to build regional capacity on the use of climate scenarios and analogues for designing adaptation options, and to provide an overview of climate modeling techniques and tools. Specialists from the hard and social sciences - both private and public sector - from Ethiopia, Kenya, Tanzania and Uganda attended the workshop.